Inclusion complex of S(-) bupivacaine and 2-hydroxypropyl-β-cyclodextrin: study of morphology and cytotoxicity - Moraes, C. M.; Araújo, D. R.; Issa, M. G.; Ferraz, H. G.; Yokaichiya, F.; Franco, M. K. K. D.; Mazzaro, I.; Lopes, P. S.; Gonçalves, M. M.; Paula, E. DE; Fraceto, L. F. [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
Local anesthetics (LA) belong to a class of pharmacological compounds that attenuate or eliminate pain by binding to the sodium channel of excitable membranes, blocking the influx of sodium ions and the propagation of the nerve impulse. S (-) bupivacaine (S(-) bvc) is a local anesthetic of amino-amide type, widely used in surgery and obstetrics for sustained peripheral and central nerve blockade. This article focuses on the characterization of an inclusion complex of S(-) bvc in 2-hydroxypropyl-ß-cyclodextrin (HP-ß-CD). Differential scanning calorimetry, scanning electron microscopy and X-Ray diffraction analysis showed structural changes in the complex. In preliminary toxicity studies, the cell viability tests revealed that the inclusion complex decreased the toxic effect (p<0.001) produced by S(-) bvc. These results suggest that the S(-) bvc:HP-ß-CD inclusion complex represents a promising agent for the treatment of regional pain. Keywords: S(-) bupivacaine; cyclodextrin; inclusion complex.
Keywords: S(-) bupivacaine; cyclodextrin; inclusion complex; Farmacotécnica